DIDACTIC CONDITIONS OF APPLICATION OF INFORMATION TECHNOLOGIES IN THE PROCESS OF HIGHER EDUCATION STUDENTS - N.O. Poberezhna (Academy of Cognitive and Natural Sciences, 2009)
In the article the methods and complex of didactic conditions of information technology appliance in the educational process of students in a higher educational establishment have been elaborated and represented.